BetterPoints: Motivating behaviour change using technology-driven incentivisation - Anne Lancaster (Frontiers Media S.A., 2015)
Background Conference theme: Using behaviour change theory to create high-quality interventions and products. BetterPoints is a localised behaviour change system that uses incentivisation, recognition and social interaction - all driven by an innovative technology. Our main method of engagement is a proprietary smartphone app. The app is part of a powerful behaviour change technology platform that allows rapid customisation, massive reward flexibility and sophisticated reporting. This includes a portal, content management system, digital dashboard and API. It is presently being used across several Local Authorities in England to motivate people to visit parks, use sustainable transport, be more active, make healthy lifestyle choices and engage with their community. Today, more than 21,000 people earn BetterPoints for positive activities in their locality, such as walking, cycling, car-sharing or attending weight loss classes. Points can be redeemed for shopping vouchers or be given to charities or community groups to turn into money for fundraising purposes. Description Our approach combines behaviour change theoretical underpinnings with deep understanding of the loyalty and rewards marketplace, digital marketing and social media. Motivating real world change involves moving from incentives to emotional investment, personal and social engagement. Extrinsic rewards can influence the formation of pro-social behaviours that continue after the rewards have stopped if participants find intrinsic and social motivation in the action itself. As illustrated by the Charness and Gneezy (2009) excerpt below: "In the case of exercise, establishing a habit by requiring multiple and frequent visits seems necessary-especially for those who have little or no previous habit of exercising. A self-commitment device, or even just a decision that would impel us to go to the gym for a month before evaluating the cost and benefit of exercising, may result in a different assessment of the net value of the activity." BetterPoints programmes take into account a number of factors from multiple models of Behaviour Change, including internal (attitudes, values, habits and personal norms) and external (incentives, constraints and social) factors. The technology platform is flexible enough to address individual change over time, meet the varied goals of targeted intervention programs and adapt to multi faceted behaviour change frameworks as they evolve. BetterPoints addresses the Motivation section of the COM-B Hub of the Behaviour Change Wheel (Michie, 2011), with incentivisation as the main intervention function. Additionally, it uses persuasion and education through communication and marketing about using the app, such as on-street posters, social media, blog-posts, emails, and mobile push-notification messages. It is possible to record the actions of those involved in order to track success and optimise rewards, at the individual and group level. For example, for a woman who has a BMI of over 30, with low self-reported activity levels, the system could reward her for taking 5 short walks a week, and after a month of 15 activities has been completed, it could give an automatic additional monthly bonus. This activity would be supported by social media, email and push notification messages encouraging her to get moving, draw attention to the benefits of activity for health, give updates on how many points she had, and encouragement to notice positive intrinsic aspects of her different choices, such as appreciating nature on a walk. The programme could then give her social rewards for going for a walk with a friend, going to exercise classes or doing several walks in one day, recording by time taken or distance covered. Rewards and incentives build up over time and in relation to what has already been achieved in the programme, all automatically recorded within the system. Case Study - Birmingham Birmingham City Council's Wellbeing team needed to capture and measure activity that fell outside of the scope of structured projects, to demonstrate the value to public health of "informal" activity in the city's parks. This project was initiated as a pilot project in September 2014 with the aim of incentivising users to increase their levels of physical activity and recording it via a smartphone app. Aims • To establish whether rewards would work as a means to capture data using formal methods • To reward further engagement and activity where that met the needs of the Council's Public Health agenda. • In the longer term to reward and incentivise a range of activity that fell outside of the scope of Active Wellbeing, from volunteering to community activities, council recycling and so on. Data Capture An extensive dataset is now produced monthly for Birmingham City Council. This dataset is cross referenced by BCC's Customer Knowledge - Corporate Strategy team to give insight into socio-economic profiles of park users, the relationship between activity in parks and Indices of Multiple Deprivation, activity levels and changes over time. A data reporting dashboard has been set up and is being developed based on feedback from this process. Ultimately these reports will be linked with economic analysis of early intervention on a range of health and social issues. Birmingham Programmes - Outcomes • The app is gaining in popularity; Registrations increasing month on month • We are engaging hard to reach groups; 46% of participants were from the top 30% most deprived areas (IMD) • Individual activity increases over time; 100% increase in average activities per active user over 7 months This case study illustrates that rewarding participants at specific locations, for repetitions, distances, speeds and/or time taken, produces a data set to demonstrate that behaviours have changed and BetterPoint programmes are high quality interventions. We work increasingly with partners who can provide other intervention functions such as environmental restructuring, to create a tailored behaviour change system to address specific needs for particular populations. Conclusions The BetterPoints system is unique in it's flexibility and ability to draw on multiple behaviour change models to create high quality interventions. Early findings from existing programmes being implemented for Local Authorities in the UK suggest that BetterPoints can demonstrate real-world behaviour change. We would like to work with academic partners to further investigate these real-world changes in behaviour and establish a robust evidence base.